Expression analysis of a pseudogene in transgenic tobacco: a frameshift mutation prevents mRNA accumulation. - Voelker, T A (1990)
Seeds of the Pinto cultivar of the common bean, Phaseolus vulgaris, are deficient in phytohemagglutinin (PHA), a lectin normally composed of two different polypeptides (PHA-E and PHA-L). In Pinto seeds, there is no PHA-E and only small amounts of PHA-L. The gene coding for the Pinto PHA-E, Pdlec1, is a pseudogene as a result of a single base pair deletion in codon 11, causing a frameshift and premature termination of translation. This mutation explains the absence of the PHA-E polypeptide but not the several-hundredfold reduction of the cytoplasmic Pdlec1 mRNA in developing seeds when compared with a normal PHA-E gene. To find the cause for this reduction in mRNA levels, we swapped gene fragments of Pdlec1 with the homologous parts of a normal PHA gene from the cultivar Greensleeves and introduced these fusions into tobacco. Analysis of the transgenic seeds showed that the Pdlec1 promoter is fully functional. We also repaired the Pdlec1 coding frame in vitro and inserted the repaired and unrepaired versions into a PHA gene expression cassette. In transgenic tobacco, both constructs showed Pdlec1 transcript accumulation in the second half of seed maturation. The single-base frame repair boosted the peak transcript levels by a factor of 40 and resulted in the synthesis of PHA-E at normal levels. We propose that the premature translational stop caused by the frameshift leads to a faster breakdown of the Pdlec1 mRNA, thereby preventing this transcript from accumulating to high levels.